2006
DOI: 10.1080/09595230600891282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of needle and syringe programme attendees and non-attendees from a high drug-using area in Sydney, New South Wales

Abstract: The aim of this study was to compare demographic and drug use profiles of non-needle and syringe programmes (NSP) attendees with NSP attendees from the same geographic area. Two data sources were used. One was from an annual national survey of injecting drug users (IDU) at NSP and analysis was restricted to survey sites in Kings Cross and Kogarah in 2003 (NSP survey). The other was from a survey of IDU who do not use NSP as their primary source of injecting equipment within the same broad geographical region (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…These findings suggest that regular utilization of needle and syringe programs can reduce HIV risks among PWID in Iran. This is consistent with findings from other studies showing that reductions in sexual and injection-related risk behaviors are related to increasing access to NSPs (Cao and Treloar 2006; Vazirian et al 2005; Noroozi et al 2016). …”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that regular utilization of needle and syringe programs can reduce HIV risks among PWID in Iran. This is consistent with findings from other studies showing that reductions in sexual and injection-related risk behaviors are related to increasing access to NSPs (Cao and Treloar 2006; Vazirian et al 2005; Noroozi et al 2016). …”
Section: Discussionsupporting
confidence: 92%
“…Fraser, 2013;Rhodes and Quirk, 1998;Seear et al, 2012;Simmons and Singer, 2006). Recent survey data, for example, indicate that over 50% of participants who reported sharing injecting equipment did so with their regular sexual partner (Iversen and Maher, 2015), with similar patterns found in earlier studies (Roux et al, 2014;Bryant et al, 2010;Cao and Treloar, 2006). This "individualising tendency" has important implications for efforts to understand and prevent the transmission of hepatitis C, particularly within couples where arguably the risk is greatest.…”
Section: Introductionmentioning
confidence: 62%
“…In 2011, Australian surveillance data indicated that the largest proportion of needle sharing incidents (approximately 50%) occurred between sexual partners (Iversen & Maher, 2012), and similar patterns have been noted elsewhere (Bryant, Brener, Hull, & Treloar, 2010;Cao & Treloar, 2006). Beyond the sharing of needle and syringes, a significant proportion of hepatitis C transmissions between sexual partners is also thought to occur through the sharing of ancillary equipments, such as filters, swabs, spoons and tourniquets (Bryant et al, 2010).…”
Section: Heterosexual Partnerships and Gendermentioning
confidence: 80%